The role of emotional intelligence in human life - Knopp, Katarzyna (Studia Psychologica: Theoria et praxis, 2006)
The author makes an attempt to explain connections between emotional intelligence and success in life. The paper is focused on such aspects of human life as interpersonal functioning, psychological and physical well-being as well as with success at school and work. The article presents review of research in which emotional intelligence was conceptualized according to Salovey and Mayer.s model or to .mixed. models. The empirical data suggest that claims of some researchers who think that emotional intelligence is a fundamental determinant of a life success, seem to be exaggerated. Although high level of emotional intelligence is connected with successful interpersonal relationships, success in school and work and general well-being, correlation coefficients are lower than expected.